Scientific-based approach pictorial storybook for eliciting creative thinking and collaborative skills - Annisa Yulistia (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2019)
This research aimed to develop a picture-story book based on scientific approach through the discovery learning method to improve students’ creative thinking and collaborative skill. This research was a research and development which adopted a model proposed by Borg Gall which step including (1) research and information collecting, (2) planning, (3) developing preliminary product, (4) prelimi-nary field testing, (5) main product revision, (6) main field testing, (7) operational product revision, (8) operational field testing, (9) final product revision, and (10) dissemination and implementation. The subject consisted of 50 students from the experimental class and 25 students from the control class. The result showed that (1) the picture-story book based on scientific approach through discovery learning method developed valid for use based on expert assessment and test result at the school with “very good” category, (2) the picture-story book based on scientific approach through discovery learning method could be used to improve students’ creative thinking and collaborative skills.